Health Promotion in Times of Uncertainty - Juvinyà Canal, Dolors (Universidad de Sonora, 2022)
According to Kickbush in 1997, health is created through an interrelation between people and their environment during their everyday life, especially where they live, love, learn, work and play. In this context, health promotion (HP) is the process that allows people to increase the control on their health to improve it ⁽¹⁾; therefore, in this process life health conditions and social determinants will have a fundamental role when it comes to understanding the health of the people.